Assessment of mechanical properties of rice husk ash modified asphalt mixture. (15th September 2017) - Arabani, Mahyar; Tahami, Seyed Amid
Highlights: The feasibility of using rice husk ash as an asphalt modifier in hot mix asphalt was investigated. The addition of RHA to asphalt binder improved the rheological and physical properties of asphalt binder. The use of RHA enhanced the Marshall stability and stiffness modulus of asphalt mixtures. Asphalt mixtures with RHA showed better rutting resistance and fatigue performance than control mixtures. Abstract: Using rice husk ash (RHA), as a waste byproduct of rice milling, in bituminous roadways provides valuable advantages such as reduction of environmental degradation, lowering construction costs and saving natural resources. However, there are limited numbers of studies on application of this material in asphalt mixture. The objective of this study was to investigate the effects of RHA as an asphalt modifier on hot mix asphalt. Bitumen blends with 5%, 10%, 15% and 20% RHA modifier. For evaluation of the rheological properties of asphalt binders, various tests including penetration grade, ductility, softening point, rotational viscosity and dynamic shear rheometer were conducted. Also, the mechanical properties of asphalt mixtures including Marshall stability, stiffness modulus, rutting resistance and fatigue behavior were assessed. The results showed that the rheological properties of bitumen were enhanced by adding RHA. Furthermore, RHA modification had positive impacts on the Marshall stability, stiffness modulus, rutting strength and fatigue performance of asphalt mixtures.